Polarization and EIS studies to evaluate the effect of aluminum concentration on the corrosion behavior of SAC105 solder alloy - Liyana, N.K.; Fazal, M.A.; Haseeb, A.S. Md. Abdul (De Gruyter Open, 2018)
This paper presents an investigation on corrosion behavior of Sn-1.0Ag-0.5Cu-XAl (X = 0, 0.1, 0.5, 1.0) by means of polarization and electrochemical impedance spectroscopy (EIS) measurements in 3.5 wt.% NaCl solution. The results show that addition of aluminum into SAC105 shifts the corrosion current density and passivation current density towards more positive values. It is also found that with an increase in aluminum concentration in SAC105 solder alloy, the corrosion current density increases and polarization resistance decreases. This suggests that SAC105 with the highest concentration of Al has the lowest corrosion resistance. In this case, the corrosion behavior seems to be attributed to anodic dissolution of aluminum and Sn-matrix.